2012
DOI: 10.5430/jct.v2n1p10
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Conceptions of Area Measurement and Their Strategies for Solving Area Measurement Problems

Abstract: This study investigated children's understanding of area measurement, including the concept of area and the area formula of a rectangle, as well as their strategic knowledge for solving area measurement problems. Twenty-two fourth-graders from three classes of a public elementary school in Taipei, Taiwan, participated in a one-on-one interview. Results show that the children who had a good understanding of the concept of area and the area formula (by using the property of multiplication) exhibited competency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
1
22
0
3
Order By: Relevance
“…Diversos estudios (D'AMORE;FANDIÑO, 2007;HUANG;WITZ, 2013;KOSPENTARIS;SPYROU;LAPPAS, 2011;ZACHAROS, 2006) han mostrado que un gran ISSN 1980-4415 DOI: http://dx.doi.org/10.1590/1980 número de estudiantes, tanto de educación primaria como de secundaria y bachillerato, poseen una comprensión limitada del área, vinculándola únicamente con el uso de cálculos que aplican de forma memorística. Esto puede ser porque los estudiantes no comprenden el significado de las fórmulas, ni cómo éstas se originan (D'AMORE;FANDIÑO, 2007).…”
Section: Medición Del áReaunclassified
See 1 more Smart Citation
“…Diversos estudios (D'AMORE;FANDIÑO, 2007;HUANG;WITZ, 2013;KOSPENTARIS;SPYROU;LAPPAS, 2011;ZACHAROS, 2006) han mostrado que un gran ISSN 1980-4415 DOI: http://dx.doi.org/10.1590/1980 número de estudiantes, tanto de educación primaria como de secundaria y bachillerato, poseen una comprensión limitada del área, vinculándola únicamente con el uso de cálculos que aplican de forma memorística. Esto puede ser porque los estudiantes no comprenden el significado de las fórmulas, ni cómo éstas se originan (D'AMORE;FANDIÑO, 2007).…”
Section: Medición Del áReaunclassified
“…El uso de los diferentes SP del área se ve restringido por el conocimiento de la fórmula del área de cuadrados y triángulos. De esta manera, se confirman resultados de investigaciones anteriores (D'AMORE;FANDIÑO, 2007;HUANG;WITZ, 2013;KOSPENTARIS;SPYROU;LAPPAS, 2011;ZACHAROS, 2006), que concluyen que el desempeño de los estudiantes queda limitado casi exclusivamente por el uso de cálculos y fórmulas, aun cuando no se precisa de éstos.…”
Section: Conclusionesunclassified
“…Faulkenberry (2003) suggests that conceptual knowledge is rich with relations, and refers to the basic mathematics constructs and relations between the ideas that illustrate mathematical procedures, and gives it a For instance, in understanding of area measurement, procedural fluency, and reflections on the accuracy of solutions for measuring areas, represents higher-order thinking skills (Lehrer, 2003). While investigating children's conceptions of Area Measurement and their strategies for solving Area Measurement problems, Huang, Witz (2012) found that children who had a good understanding of the concept of area and the area formula (by using the property of multiplication) exhibited competency in identifying geometric shapes, using formulas for determining areas, and self-correcting Many mathematics skills are involved in problem-solving. However, large numbers of students have not acquired the basic skills they need in mathematics.…”
Section: Conceptual Understanding and Procedural Knowledgementioning
confidence: 99%
“…(2) Assigns meaning to numerical quantities (i.e., numbers) for the length and width of 2-D figures (Reynolds & Wheatley, 1996); thus, relates the numbers to symbolic representations of geometric properties and formulas for (surface) area measurement and unit conversion (Battista, 2004;Huang & Witz, 2013). Battista, 2004;Reynolds & Wheatley, 1996) or in finding the areas of irregular 2-D figures.…”
Section: ↑ Transition Points Of 35b To 4bmentioning
confidence: 99%